An integrative review of the research outputs in leadership behavior in the educational management/development departments of five graduate schools in Metro Manila - Azikin, Djaenabong (Animo Repository, 1988)
This study presents an integrative review of research outputs on leadership behavior in the Educational Management and Development Education departments in 5 graduate schools in Metro Manila. It likewise analyzes the relationship between the characteristics and work environment of administrators and leadership behavior. Further, the study plans to present a profile of theses and dissertations on leadership behavior in the 5 schools showing degree program and year of completion level, type and location of school research design sampling procedure statistical treatment and integrative findings. It examines the relationship, if any, between administrators' leadership behavior and administrator-related variables as sex, age, educational qualification, and length of experience and school-related variables as level, type, and location of school. The research design utilizes the descriptive method of research integration using 32 samples of theses and dissertations. Multiple regression analysis is employed as statistical treatment. Findings revealed that there is no significant relationship between level of school and leadership behavior, the Pearson r -.214.348 at 0.05 level of significance no significant relationship between type of school and leadership behavior, the Pearson r-.191.348 at 0.05 level of significance and that there is no significant relationship between location of school and leadership behavior, Pearson r.289.348 at 0.05 level of significance. Based on the findings of research outputs on leadership behavior, the conclusions drawn were that no significant relationship exists between level, type, and location of school and leadership behavior. Leadership behavior may not be predicted. This confirmed the Contingency Model of Fiedler that any leadership style can be effective depending on the situation.